1997
DOI: 10.1515/zna-1997-1104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Studies of Ferroelectric Phase Transition in Gly-H3PO3 Crystals

Abstract: The temperature behaviour of the longitudinal and transverse ultrasound wave velocities and attenuation in the region of the ferroelectric phase transition (T c -225 K.) of the glycine phosphite (Gly-H 3 P0 3 ) crystals is studied. The obtained results are considered within the framework of phenomenological theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…The elastic properties investigated in the piezoelectric studies revealed, instead of the remarkable jump of the elastic stiffness and compliance at T C expected on the basis of the ultrasonic measurements reported in [9][10][11] and Brillouin scattering experiments [12], a very small anomaly of the elastic stiffness and compliance.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The elastic properties investigated in the piezoelectric studies revealed, instead of the remarkable jump of the elastic stiffness and compliance at T C expected on the basis of the ultrasonic measurements reported in [9][10][11] and Brillouin scattering experiments [12], a very small anomaly of the elastic stiffness and compliance.…”
Section: Discussionmentioning
confidence: 65%
“…Information on the order of the phase transition and coupling between the order parameter and elastic properties of the crystal was inferred from ultrasonic studies [9][10][11] and a Brillouin scattering experiment [12]. The experiments revealed a sound velocity jump at T C and the ultrasonic study results [9] indicated a pseudoproper character of the phase transition at T C .…”
Section: Introductionmentioning
confidence: 99%
“…It is a consequence of a weak coupling due to the layered arrangement along the a-axis and the hydrogen bonding of ionic groups along the c-axis. The observed temperature anomalies of elastic constants in the vicinity of the T c [15] were explained as a manifestation of the probably pseudoproper origin of ferroelectricity in GPI due to anharmonic interaction of the order parameter with deformation of the crystal lattice.…”
Section: Cooh]mentioning
confidence: 93%
“…Since the phase transition temperature is shifted to 322 K by deuterium substitution for hydrogen [4,5], ordering of protons in hydrogen bonds expects to be important in the phase transition. The phase transition has been proved to have order-disorder nature from a critical slowing down of the dielectric dispersion of Debye type [4][5][6], hydrostatic pressure effect study [7], ultrasonic study [8][9][10], photopyroelectric study [11], Brillouin scattering [12,13], Raman scattering [4,14], and EPR study [15]. Recently, it is revealed by a series of neutron and X-ray diffraction experiments [16][17][18][19][20] that the hydrogen or deuteron in the bonds are disordered in the paraelectric phase and are ordered in the ferroelectric phase, respectively.…”
Section: Introductionmentioning
confidence: 99%